PROGRESIFITAS MAHKAMAH KONSTITUSI BAGI PERLINDUNGAN HUKUM TERHADAP PETANI GUREM (ANALISIS PUTUSAN MK RI NOMOR 99/PUU-X/2012) - Winardi Winardi (Legal Spirit, 2017)
The Constitutional Court made a progressive legal breakthrough by asserting the rights of smallholders through the verdict on the testing of Plant Cultivation System Law. The Court stated that small farmers are exempt from licensing in making plant breeding and producing seeds. Criminalization of small farmers should be avoided. In view of this decision, a legislation is required on legal protection of farmers capable of ensuring (a) the right of peasants to the main resources, capital and production factors; (b) the right to technology in the form of seeds, fertilizers and plant protection; (c) the right to post-harvest handling and agricultural products processing and; (d) rights to the distribution and marketing of agricultural products. Keywords: Farmers and Legal Protection